REVITALISASI NASIONALISME DIGITAL MELALUI APLIKASI BERBASIS TEKNOLOGI INFORMASI DI ERA MASYARAKAT 5.0 - Abdurrohim, Iim; Tri Hastuti; Dhabitah, Khairani Ghassan (LEMBAGA PUSAT KAJIAN KEBANGSAAN/PUSKAB UKRI, 2025)
The rapid digitalization of society presents both opportunities and challenges for cultivating nationalism among younger generations. Traditional expressions of nationalism often fail to resonate with digital natives, requiring more adaptive and participatory approaches. This study aims to explore how a mobile application, e-Nasionalis, can be utilized to strengthen civic values and digital nationalism among Indonesian youth. Employing a mixed-methods approach, the research integrates the development and limited testing of the application with user feedback analysis from 60 participants, including students, university youth, and digital community members. Features of the app include civic education modules, daily acts of nationalism, and a hoax reporting tool. Quantitative data showed a high level of user engagement and satisfaction, while qualitative insights revealed positive changes in users’ understanding and practice of nationalism in everyday digital life. The findings suggest that the integration of information technology and political education can provide innovative civic learning platforms that are relevant, engaging, and impactful in the context of Society 5.0.